Pelaksanaan Supervisi Akademik Dalam Meningkatkan Kompetensi Guru: Systematic Literature Review - Fitri Aprilianty; Isna Susmita; Mirna Rasuani (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to examine the contribution of academic supervision to improving teacher competence through a Systematic Literature Review approach to 15 articles published in the last decade. The focus of the study includes the effectiveness of supervision, implementation techniques, teacher competence results, and supporting and inhibiting factors. The findings show that structured and ongoing academic supervision improves teachers’ pedagogical, professional, and technical competence. Techniques such as classroom observation and technical guidance have proven effective, but their implementation is constrained by time, workload, and low understanding. The novelty of this study lies in the comprehensive mapping across levels of education and the identification of contextual reflective supervision practices. Its contribution is as a basis for formulating collaborative academic supervision strategies based on teachers’ real needs to support the transformation of national education quality.